ChemInform Abstract: Structures and Reactivities of Iminium Ions Derived from Substituted Cinnamaldehydes and Various Chiral Imidazolidin‐4‐ones. Issue 44 (4th November 2014) - An, Feng; Paul, Shyeni; Ammer, Johannes; Ofial, Armin R.; Mayer, Peter; Lakhdar, Sami; Mayr, Herbert
Abstract The reaction of the imidazolidinonium hexafluorophosphate with cinnamic aldehydes provides a range of iminium hexafluorophosphates.